Cooperation the Governments of Indonesia and Australia Improves the Quality of Human Resources Through the Australia Awards Scholarship Program 2017-2022 - Agung Yudhistira Nugroho; Natalia Esther (Budapest International Research and Critics University, 2022)
Globalization encourages mobility and human reach. New challenges emerge to test the community's readiness. Based on the Global Talent Competitiveness Index, Indonesia is ranked 65th out of 132 countries. Research International Labor Organization indicates that nearly 20% of the Indonesian workforce does not qualify for the work they are doing. This data shows the low quality of education in Indonesia, especially the level of higher education. This journal examines Australia-Indonesia's efforts to meet the need to improve the quality of human resources through the Australian Awards program. Based on data from the final report of the AAI program, although 26% of scholarship participants came from Indonesia, it did not adequately represent the entire population of undergraduate graduates. This has been constrained by budget cuts, a change in Australian policy direction and successful promotions. This scholarship is known to be prestigious, but unfortunately the impact is not so significant on the development of the quality of human resources in Indonesia.